The dynamics of some extreme doubly stochastic quadratic operators - Shahidi, Farruh; Ganikhodzhaev, Rasul; Abdulghafor, Rawad Abdulkhaleq Abdulmolla (IDOSI Publications, 2013)
We provide an example of Lyapunov for doubly stochastic operators on a finite dimensional simplex. Besides we study the limit behavior of the trajectories of some extreme doubly stochastic operators on two dimensional simplex. We prove that except for certain points the trajectories of extreme doubly stochastic operators tend to the center of two dimensional simplex.